Statens udenlandske låntagning og gæld fra 1959 til 1991: En personlig beretning - Niels Erik Sørensen (Danmarks Nationalbank, 2004)
– This paper deals with Danish Government Foreign Borrowing and Debt Administration in the period 1959 to 1991 the Nationalbank succeeded the Ministry of Finance as the administrator.
Keywords: 330; Öffentliche Schulden; Internationale Staatsschulden; Dänemark